Anion‐Directed Conformation Switching and Trigonal Distortion in Hexakis(methylamine)nickel(II) Cations. Issue 30 (31st August 2022) - Sugiarto,; Minato, Takuo; Sakiyama, Hiroshi; Sadakane, Masahiro
Abstract: The homoleptic [Ni(NH2 CH3 )6 ] 2+ cations have dozens of energetically feasible conformational isomers (conformers), and we herein show their conformation is tunable using counter anions. The reaction of Ni(NO3 )2 or NiCl2 with aqueous methylamine in dimethylformamide gave [Ni(NH2 CH3 )6 ](NO3 )2 (1 ) or [Ni(NH2 CH3 )6 ]Cl2 (2 ) in which methylamine ligands have axial or equatorial orientation with respect to the three‐fold principal axis, respectively. Interestingly, the conformation of methylamine ligands affects geometry around nickel(II) so that the nickel octahedron is trigonally compressed in 1, whereas it is trigonally elongated in 2, causing different visible light absorption properties between 1 and 2 . Density functional theory calculations showed that nitrate anions stabilize the axial conformer through two‐point hydrogen bonding interactions with methylamines, whereas spherical chloride anions promote deformation of the axial conformer into the equatorial conformer through formation of three‐point hydrogen bonding interactions. Abstract : Two conformational isomers of hexakis(methylamine)nickel(II) cations – axial and equatorial – were selectively trapped using nitrate and chloride anions. The nickel octahedron is compressed in the axial conformation while it is elongated to minimize steric repulsion in the equatorial conformation. Density functional theory calculations reveal that anions facilitate conformational switching though hydrogen bonding interactions in the secondary coordination sphere.